Pengaruh Kualitas Pelayanan, Harga, Dan Word Of Mouth Terhadap Keputusan Pembelian Konsumen pada Dimsum Kaki Lima di Bandar Lampung - Extevanus, Leonaldi; Sari, Wenny Permata (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research aims to determine the influence of service quality, price, and word of mouth on consumer purchasing decisions for street food dimsum in Bandar Lampung. This research has an unknown population so the researchers used the Lemshow formula in determining the research sample, so the sample size used in this research was 100 street food dimsum consumers in Bandar Lampung. This research is a quantitative research, where the researcher will test the effect of the independent variable on the dependent variable using statistics with the help of the SPSS 25 analysis tool. The tests that will be carried out in this research are the multiple linear test, the coefficient of determination test, the t test and the F test. Based on the results data analysis, it can be concluded that Service Quality, Price, and Word of Mouth have a positive effect on Purchasing Decisions.